Relationship between Measles Vaccination Status and Measles Incidence in Toddlers - Rahmawati S; Joko Sapto Pramono; Tini (Indonesian Journal of Sport Management and Physical Education, 2023)
Measles is a highly contagious disease caused by a virus and can result in death. Before the introduction of the Measles vaccine, major epidemics occurred causing deaths every year. However, after immunization, the number of cases of measles decreased dramatically. This study aims to determine the relationship between measles vaccination status and the incidence of measles in toddlers in the working area of ​​UPT Puskesmas Sambaliung. This type of quantitative research with a research design using a Case Control survey. A sample of 62 people took data on measles vaccination status and measles incidence from secondary C-I data and visits to toddler polyclinics and then recapitulated on the observation sheet. Then the data were analyzed univariately and bivariately using the Chi Square test. The results of the chi square test obtained a value of p = 0.042 <0.05. This indicates that there is a significant relationship between measles vaccination status and the incidence of measles in toddlers in the working area of ​​the UPT Puskesmas Sambaliung.